Process simulation and evaluation for NH3/CO2 separation from melamine tail gas with protic ionic liquids - Duan, Yuanmeng; Zhan, Guoxiong; Chang, Fei; Shi, Sensen; Zeng, Shaojuan; Dong, Haifeng; Abildskov, Jens; Kjøbsted Huusom, Jakob; Zhang, Xiangping (Separation and purification technology, 2022)
•Two new process of NH3/CO2 separation with ionic liquids was designed.•Reliable thermodynamics models were built and verified with experimental data.•High fidelity benchmarking of water scrubbing versus IL-based processes.•TSC of IL-En process can be reduced by 61% than traditional water scrubbing. Melamine production is known to produce a tail gas with a significant amount of NH3 and CO2. The most common separation methods applied to melamine tail gas are water scrubbing and urea co-production technology. With good stability, non-volatility and tailored properties, ionic liquids (ILs) are regarded as vital potential solvents for gas separation. Therefore, two new process technologies, one is the ionic liquid-based process (IL-0), and the other is the enhanced ionic liquid process (IL-En) was employed and evaluated for energy and cost efficiency. The IL-En employs stripping on the treatment of melamine tail gas. The protic ionic liquid named 1-butyl imidazolium bis (trifluoromethylsulfonyl) imide ([Bim][NTf2]) was selected for the evaluation of the melamine tail gas cleaning process. Thermodynamic data were fitted to the NRTL equations. Three full process flowsheets were simulated in Aspen Plus V11 TM. A basic and an enhanced ionic liquid process (IL-0 and IL-En), a conventional water scrubbing (WS) technology as a comparison, process sensitivity analysis and energy/economic evaluation were carried out. The results showed that the total separation cost of the IL-En can be reduced by 61% compared to that of the WS process. Moreover, the IL-based flowsheet is simpler than WS and avoids wastewater discharge.